Legal Protection For Government Employees With Work Agreements (PPPK) In Unilateral Termination Of Employment Contracts - Marlina Arifin; Sandi Aprianto; Ferawati Royani (Multidisciplinary Journals, 2026)
Government Employees with Employment Contracts (Pegawai Pemerintah dengan Perjanjian Kerja/PPPK) are public personnel who engage in employment relationships based on employment contracts with government institutions for a specified period. Such employment relationships give rise to rights and obligations for the parties, which are subject to the provisions of contract law. In practice, unilateral termination of employment contracts by the government against PPPK frequently occurs before the expiration of the agreed contract period. This condition gives rise to legal issues, particularly concerning the protection of PPPK’s rights as parties to a contractual employment relationship. This study aims to analyze the legal protection afforded to PPPK who experience unilateral termination of employment contracts by the government, as well as to examine the legal remedies available to PPPK from the perspective of civil law. The research method employed is normative legal research using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively. The analysis focuses on the PPPK employment contract as the source of the legal relationship and on the principles of civil law governing the performance and termination of contracts. The results of the study indicate that legal protection for PPPK who experience unilateral termination of employment contracts by the government is derived from the contractual employment relationship, which is subject to the civil law regime. PPPK holds the status of a private legal subject with the right to certainty of employment duration and fulfillment of contractual obligations as agreed. Unilateral termination of employment contracts that contradicts the employment agreement may be classified as breach of contract or an unlawful act. In such circumstances, PPPK may pursue civil legal remedies in the form of breach of contract claims and/or tort claims to seek compensation and restoration of rights. This study emphasizes that the application of the principles of contractual justice and good faith is essential to ensuring effective legal protection for PPPK against unilateral termination of employment contracts by the government.